Hydrophilic perovskite material and preparation method and application thereof
By constructing a hydrophilic perovskite material coating on the surface of the zinc metal anode, the problems of zinc dendrite growth and hydrogen evolution side reaction are solved, improving the electrochemical performance and stability of zinc-ion batteries, making them suitable for industrial applications.
Patent Information
- Application Number
- CN202511229874.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-29
- Publication Date
- 2025-12-19
AI Technical Summary
Zinc metal anodes in zinc-ion batteries suffer from zinc dendrite growth, interface instability, and hydrogen evolution side reactions, leading to reduced battery stability and cycle life.
A hydrophilic perovskite material coating is constructed on the surface of a zinc metal anode. The hydrophilic functional groups regulate ion transport, promote uniform deposition, and inhibit zinc dendrite formation and hydrogen evolution reaction.
It significantly improves the electrochemical performance of zinc-ion batteries, enhances interface stability, extends battery cycle life, and reduces costs, making it suitable for industrial applications.
Smart Images

Figure CN121158823A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a perovskite material, specifically a hydrophilic perovskite material and its preparation method, as well as its application in zinc metal electrodes and zinc-ion batteries, belonging to the field of zinc-ion battery technology. Background Technology
[0002] Modern society requires energy to drive its development. The depletion of non-renewable energy sources, such as fossil fuels, and the resulting pollution have spurred extensive research and rapid development of renewable energy sources like wind and solar power. However, these new energy sources are subject to environmental impacts, resulting in intermittency and volatility, necessitating the development of energy storage systems. Aqueous zinc-ion batteries (AZIBs) have become a highly promising candidate in the energy storage field due to their excellent energy storage characteristics, high safety, and abundant resource reserves. The zinc metal anode, a core component of the battery, exhibits high electrochemical stability, a low redox potential (-0.76V vs. SHE), and a high specific capacity (820 mAh g⁻¹). -1 5855 mAh⋅cm -3 While zinc anodes offer advantages, the deposition / dissolution process inevitably encounters problems such as uneven deposition leading to zinc dendrite growth, interfacial instability, and hydrogen evolution byproducts. The most serious issue is the formation and growth of zinc dendrites. Dendrite tips are prone to breakage, and after losing electrical contact with the substrate, they detach, forming free "dead zinc," resulting in a significant loss of active zinc and disrupting the battery's stable structure. Furthermore, the continuous growth of zinc dendrites can puncture the separator, causing a short circuit and rendering the battery unusable. Therefore, constructing a suitable interfacial layer on the zinc anode surface, controlling the ion transport process, forming uniform zinc deposition, and suppressing dendrite formation are crucial for improving the electrochemical performance of AZIBs.
[0003] Industry researchers have made some efforts to address the problems of zinc dendrite growth, interface instability, and hydrogen evolution side reactions faced by zinc metal anodes. For example, artificial modification of the SEI during the protection process of zinc metal anodes is carried out. However, this method has strict requirements for reaction conditions, is not environmentally friendly, and is not conducive to industrial production. Another example is the addition of electrolyte additives. However, this method increases costs and may also affect the coulombic efficiency and rate performance of the battery. Summary of the Invention
[0004] The main objective of this invention is to provide a hydrophilic perovskite material and its preparation method, so as to overcome the shortcomings of the prior art.
[0005] Another object of the present invention is to provide the application of the hydrophilic perovskite material.
[0006] To achieve the aforementioned objectives, the technical solution adopted by this invention includes: This invention provides a hydrophilic perovskite material with the chemical formula A. x B y X z The A-site element and the B-site element include two or more combinations of K, Na, Mg, Ca, Sr, Ba, Bi, Sn, Pb, Zn, Ti, V, Cr, Mn, Fe, Co, Ni, and Cu. x+y=2, X includes O or OH. When X is O, z=3, and when X is OH, z=6. The surface of the hydrophilic perovskite material has hydrophilic functional groups.
[0007] This invention also provides a method for preparing a hydrophilic perovskite material, comprising: A metal salt containing an A-site element, a metal salt containing a B-site element, and a substance that can provide hydrophilic functional groups are uniformly mixed and subjected to a first reaction to obtain a hydrophilic perovskite material. Alternatively, the metal salt containing the A-site element, the metal salt containing the B-site element, and the first organic solvent are uniformly mixed and a second reaction is carried out, and the pH value is adjusted to alkaline to obtain the perovskite precursor. The perovskite precursor is sintered to obtain perovskite material; The perovskite material is subjected to a third reaction with a substance that can provide hydrophilic functional groups to obtain a hydrophilic perovskite material.
[0008] This invention also provides a hydrophilic perovskite-carbon composite material, comprising: the aforementioned hydrophilic perovskite material and a carbon matrix material, wherein the hydrophilic perovskite material and the carbon matrix material are uniformly distributed in the carbon matrix material.
[0009] This invention also provides a method for preparing a hydrophilic perovskite carbon composite material, comprising: A hydrophilic perovskite material is obtained by uniformly mixing a metal salt containing an A-site element, a metal salt containing a B-site element, a carbon matrix material, and a substance that can provide hydrophilic functional groups, and then carrying out a fourth reaction. Alternatively, the metal salt containing the A-site element, the metal salt containing the B-site element, the first organic solvent, and the carbon matrix material are uniformly mixed and subjected to the fifth reaction, and the pH value is adjusted to alkaline to obtain the perovskite precursor carbon composite material. The perovskite precursor carbon composite material is sintered to obtain a perovskite carbon composite material. The perovskite-carbon composite material is subjected to a sixth reaction with a substance that can provide hydrophilic functional groups to obtain a hydrophilic perovskite-carbon composite material.
[0010] The present invention also provides the application of the above-mentioned hydrophilic perovskite material or hydrophilic perovskite carbon composite material in the zinc metal anode of zinc-ion batteries.
[0011] Accordingly, embodiments of the present invention also provide a hydrophilic perovskite coating, which is obtained by coating the above-mentioned hydrophilic perovskite material or hydrophilic perovskite material carbon composite material onto the surface of a zinc metal anode.
[0012] Furthermore, this embodiment of the invention also provides a zinc-ion battery, wherein the surface of its zinc metal negative electrode is provided with the aforementioned hydrophilic perovskite coating.
[0013] Compared with the prior art, the beneficial effects of the present invention include at least the following: 1) This invention, by coating the zinc electrode surface with a hydrophilic perovskite coating, exhibits kinetic regulation and can significantly improve the electrochemical performance of zinc batteries; the hydrophilic functional groups in the coating can reduce the nucleation barrier during zinc deposition, uniform ion flux, and promote Zn deposition. 2+ The uniform deposition of ions effectively inhibits the occurrence and growth of zinc dendrites; at the same time, they form strong hydrogen bonds with water molecules, inhibiting hydrogen evolution reaction and other by-product reactions, and enhancing interfacial stability. 2) The hydrophilic perovskite coating of the present invention is relatively simple to prepare and coat, and has low cost. It can effectively suppress hydrogen evolution side reaction and zinc dendrite formation, and significantly improve cycle performance, rate performance and low temperature performance, thus extending the cycle life of the battery. 3) The zinc metal anode assembled by the present invention exhibits excellent stability at different current densities, which is of practical significance for accelerating the industrialization of zinc-ion batteries. Attached Figure Description
[0014] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0015] Figure 1A and Figure 1B This is a transmission electron microscope image of the ZnSn(OH)6-CNT composite material prepared in Example 1 of this invention; Figure 2 This is a transmission electron microscope image of the hydroxyl-modified SrTiO3-CNT composite material prepared in Example 2 of the present invention; Figure 3 The X-ray photoelectron spectrum of the SnCaO3-CNT composite material prepared in Example 3 of this invention; Figure 4 The scanning electron microscope image and elemental distribution map of the hydroxyl-modified SnZnO3-CNT composite material prepared in Example 4 of this invention are shown. Figure 5A and Figure 5B The hydroxyl-modified BaSn prepared in Example 5 of this invention 0.5 Zn 0.5 X-ray photoelectron spectroscopy of O3-CNT composite material; Figure 6 The Raman spectrum of the carboxyl-modified SnZnO3-CNT composite material prepared in Example 6 of this invention; Figure 7 The carboxyl-modified CaSn prepared in Example 7 of this invention 0.5 Zn 0.5 X-ray photoelectron spectroscopy of O3-Gr composite material; Figure 8A and Figure 8B The images are scanning electron microscope (SEM) images of the original zinc electrode and the zinc electrode coated with the hydroxyl-modified MgMnO3-CNT composite material prepared in Example 8 of this invention, respectively. Figure 9A and Figure 9B The original zinc electrode and the hydroxyl-modified BaSn prepared in Example 9 of this invention are respectively used. 0.5 Zn 0.5 Comparison of wetting angles on zinc electrode surfaces of O3-Gr composite materials; Figure 10A and Figure 10B These are performance comparison graphs of zinc-zinc symmetric cells based on hydrophilic perovskite-coated zinc electrodes and original zinc electrodes under different current densities in Example 10 of the present invention. Figure 11 This is a comparison chart of the rate performance of zinc-zinc symmetric cells based on hydrophilic perovskite-coated zinc electrodes and original zinc electrodes in Example 11 of the present invention. Figure 12A and Figure 12B The images show a comparison of the corrosion roughness of the original zinc electrode and the hydrophilic perovskite-coated zinc electrode in Example 12 of this invention before and after electrochemical testing. Figure 13 This is a TEM image of the pure hydrophilic perovskite material ZnSn(OH)6 prepared in Example 15 of this invention; Figure 14 This is a comparison of the electrochemical performance of the Zn electrode before and after modification with pure hydrophilic perovskite material SrTiO3 prepared in Example 16 of this invention; Figure 15 This is a SEM image of the pure perovskite material SnZnO3 modified Zn anode after cycling, prepared in Example 17 of this invention. Detailed Implementation
[0016] In view of the problems of low cycle life caused by dendrite growth and hydrogen evolution side reactions in existing zinc metal anodes, the inventors of this application, through long-term research and extensive practice, have proposed the technical solution of this application, which mainly adopts an A modified with a hydrophilic functional group. x B y X z A perovskite-structured material is used as a surface conditioning coating for zinc metal electrodes. This coating has a kinetic regulating effect on the negative electrode surface, homogenizing the ion flux and promoting Zn production. 2+ Uniform ion deposition effectively inhibits the occurrence and growth of zinc dendrites, improves battery cycle performance, and extends battery cycle life.
[0017] The following will further explain the technical solution, its implementation process, and its principles. However, it should be understood that within the scope of this invention, the above-mentioned technical features of this invention and the technical features specifically described below (in embodiments) can be combined with each other to form new or preferred technical solutions. Due to space limitations, they will not be described in detail here.
[0018] As one aspect of the technical solution of this invention, the chemical formula of a hydrophilic perovskite material is A. x B y X z Where x+y=2, X includes O or OH, when X is O, z=3, when X is OH, z=6; the A-site element and the B-site element can be a combination of two or more of K, Na, Mg, Ca, Sr, Ba, Bi, Sn, Pb, Zn, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, but are not limited to these.
[0019] In some embodiments, the surface of the hydrophilic perovskite material has hydrophilic functional groups, which may be one or more combinations of hydroxyl, carboxyl, sulfonic acid, amino, etc., but are not limited thereto.
[0020] Furthermore, X may also include a small amount of doped F element.
[0021] As one aspect of the technical solution of the present invention, the preparation method of a hydrophilic perovskite material includes: uniformly mixing a metal salt containing an A-site element, a metal salt containing a B-site element, and a substance capable of providing hydrophilic functional groups and carrying out a first reaction to obtain a hydrophilic perovskite material.
[0022] In some embodiments, the metal salt containing the A-site element includes one or more combinations of halides, acetates, etc., containing the A-site element, but is not limited thereto.
[0023] In some embodiments, the metal salt containing the B-site element includes one or more combinations of B-site element-containing halide salts, acetates, etc., but is not limited thereto.
[0024] Furthermore, the metal salt containing the A-site element and the metal salt containing the B-site element can specifically be one or more combinations of SnCl4, ZnCl2, TiCl4, SrCl2, CaCl2, ZnAc2, BaCl2, NaSnO3, MnBr2, MgBr2, etc., but are not limited to these.
[0025] In some embodiments, the mass ratio of the metal salt containing the A-site element, the metal salt containing the B-site element, and the substance capable of providing hydrophilic functional groups is (0.8~23):(0.5~21):(0.2~5).
[0026] In some implementations, the temperature of the first or second reaction is 0~80°C, and the time is 0.5~18h.
[0027] In some embodiments, the substance capable of providing hydrophilic functional groups may be one or more combinations of thioglycerol, citric acid, ethylenediaminetetraacetic acid, amino-polyethylene glycol-carboxyl, ethylene glycol, ethanol, etc., but is not limited thereto.
[0028] As another aspect of the technical solution of the present invention, a method for preparing another hydrophilic perovskite material may include: The metal salt containing the A-site element, the metal salt containing the B-site element, and the first organic solvent are uniformly mixed and a second reaction is carried out. The pH value is adjusted to alkaline to obtain the perovskite precursor. The perovskite precursor is sintered to obtain perovskite material; The perovskite material is subjected to a third reaction with a substance that can provide hydrophilic functional groups to obtain a hydrophilic perovskite material.
[0029] The metal salts containing A-site elements, metal salts containing B-site elements, and substances that can provide hydrophilic functional groups are all as previously described and will not be repeated here.
[0030] In some embodiments, the mass ratio of the metal salt containing the A-site element to the metal salt containing the B-site element is (0.8~23):(0.5~21).
[0031] In some embodiments, the first organic solvent includes one or more combinations of N,N-dimethylformamide, dimethyl sulfoxide, etc., but is not limited thereto.
[0032] Furthermore, the preparation method includes adjusting the pH value to alkaline with triethylamine.
[0033] In some embodiments, the sintering treatment is carried out at a temperature of 500-1000°C for a time of 0.5-12 hours, and the sintering atmosphere used includes an air atmosphere or an inert atmosphere.
[0034] In some embodiments, the preparation method includes: dispersing the perovskite material in a second organic solvent, adding a substance capable of providing hydrophilic functional groups under stirring, and carrying out a third reaction at room temperature for 0.5 to 5 hours to obtain the hydrophilic perovskite material.
[0035] Furthermore, the second organic solvent may include, but is not limited to, methanol.
[0036] In some embodiments, the mass ratio of the perovskite material to the substance capable of providing hydrophilic functional groups is (1~12):(0.2~5).
[0037] As another aspect of the technical solution of the present invention, it also relates to a hydrophilic perovskite material carbon composite material, comprising: the hydrophilic perovskite material and a carbon matrix material, wherein the hydrophilic perovskite material and the carbon matrix material are uniformly distributed in the carbon matrix material.
[0038] In some embodiments, the carbon matrix material may include one or more of carbon nanotubes, graphene, acetylene black, Ketjen black, etc., but is not limited thereto.
[0039] In some embodiments, the content of hydrophilic perovskite material in the hydrophilic perovskite carbon composite material is 30~80 wt%.
[0040] As another aspect of the technical solution of the present invention, it also relates to a method for preparing a hydrophilic perovskite carbon composite material, which includes: uniformly mixing a metal salt containing an A-site element, a metal salt containing a B-site element, a carbon matrix material, and a substance capable of providing hydrophilic functional groups and carrying out a fourth reaction to obtain a hydrophilic perovskite material.
[0041] In some embodiments, the mass ratio of the metal salt containing the A-site element, the metal salt containing the B-site element, the carbon matrix material, and the substance capable of providing hydrophilic functional groups is (0.8~23):(0.5~21):(0.02~0.1):(0.2~5).
[0042] As another aspect of the technical solution of the present invention, it also relates to a method for preparing another hydrophilic perovskite carbon composite material, comprising: The metal salt containing the A-site element, the metal salt containing the B-site element, the first organic solvent, and the carbon matrix material are uniformly mixed and subjected to the fifth reaction. The pH value is adjusted to alkaline to obtain the perovskite precursor carbon composite material. The perovskite precursor carbon composite material is sintered to obtain a perovskite carbon composite material. The perovskite-carbon composite material is subjected to a sixth reaction with a substance that can provide hydrophilic functional groups to obtain a hydrophilic perovskite-carbon composite material.
[0043] In some embodiments, the mass ratio of the metal salt containing the A-site element, the metal salt containing the B-site element, and the carbon matrix material is (0.8~23):(0.5~21):(0.02~0.1).
[0044] In some embodiments, the temperature of the fourth or fifth reaction is 0~80°C and the time is 0.5~18h.
[0045] In some embodiments, the sintering treatment is carried out at a temperature of 500-1000°C for a time of 0.5-12 hours, and the sintering atmosphere used includes an air atmosphere or an inert atmosphere.
[0046] In some embodiments, the preparation method includes: dispersing the perovskite carbon composite material in a second organic solvent, adding a substance capable of providing hydrophilic functional groups under stirring, and carrying out a sixth reaction at room temperature for 0.5 to 5 hours to obtain the hydrophilic perovskite carbon composite material.
[0047] The metal salt containing the A-site element, the metal salt containing the B-site element, the substance that can provide a hydrophilic functional group, the first organic solvent, and the second organic solvent are all as previously described and will not be repeated here.
[0048] In some embodiments, the mass ratio of the perovskite carbon composite material to the substance capable of providing hydrophilic functional groups is (1~23):(0.2~5).
[0049] As another aspect of the technical solution of the present invention, it also relates to the application of the aforementioned hydrophilic perovskite material or hydrophilic perovskite carbon composite material in the zinc metal anode of zinc-ion batteries.
[0050] Accordingly, another aspect of the present invention provides a hydrophilic perovskite coating, which is obtained by coating the aforementioned hydrophilic perovskite material or a hydrophilic perovskite-carbon composite material onto the surface of a zinc metal anode. The present invention significantly improves the electrochemical performance of zinc-ion batteries by coating a hydrophilic perovskite coating onto the surface of a zinc metal electrode using a simple method.
[0051] In some embodiments, the thickness of the hydrophilic perovskite coating does not exceed 20 µm.
[0052] The hydrophilic perovskite coating of the present invention has a relatively simple preparation and coating process. The hydrophilic functional groups in the coating can reduce the nucleation barrier during zinc deposition, uniform ion flux, and effectively suppress zinc dendrite formation. At the same time, it forms strong hydrogen bond interactions with water molecules, inhibiting hydrogen evolution reaction and other by-product reactions, and enhancing interface stability.
[0053] Correspondingly, another aspect of the technical solution of the present invention also provides a zinc-ion battery, wherein the zinc metal negative electrode surface of the zinc-ion battery is provided with the aforementioned hydrophilic perovskite coating.
[0054] The battery prepared by the present invention based on zinc metal electrode coated with hydrophilic perovskite coating exhibits excellent rate performance and good cycle life at high current density.
[0055] In summary, this invention modifies A with hydrophilic functional groups. x B y X Z A hydrophilic perovskite material is coated onto a zinc metal electrode as an interface coating material. Its surface hydrophilic OH functional groups capture active water, promoting uniform wetting of the aqueous electrolyte on the negative electrode surface. Simultaneously, the A-type electrode modified with these hydrophilic functional groups… x B y X Z Hydrophilic perovskite reinforced Zn 2+ The coating is uniformly distributed on the electrode surface during deposition, reducing the formation of zinc dendrites. Strong hydrogen bonds form between the coating and water molecules, inhibiting hydrogen evolution of active water at the negative electrode, improving interfacial stability, and promoting the desolvation of hydrated zinc ions. Compared with existing technologies, the method provided by this invention is simple to operate, low in cost, easy to scale up for production, and produces an ordered coating structure with good stability and reliable performance. Batteries assembled with this zinc metal negative electrode exhibit excellent stability at different current densities, which is of practical significance for accelerating the industrialization of zinc-ion batteries.
[0056] The technical solution of the present invention will be further described in detail below with reference to several preferred embodiments and accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. It should be noted that the following embodiments are intended to facilitate understanding of the present invention, and do not constitute any limitation thereof. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0057] Example 1 2.08 g SnCl4 and 0.888 g ZnCl2 were dissolved in 100 ml ethylene glycol and magnetically stirred until fully dissolved. 0.05 g CNT was added to the resulting solution. After the addition was complete, stirring was continued at room temperature overnight, followed by standing for 6 hours. The solution was then washed with water and ethanol to obtain a precipitate. The precipitate was dried in an oven at 80°C for 12 hours. In this embodiment, ethylene glycol was used as both a solvent and a hydroxyl source.
[0058] The morphology of the final product was characterized using TEM. Figure 1A and Figure 1B This is a transmission electron microscope (TEM) image of the ZnSn(OH)6-CNT composite material prepared in this embodiment.
[0059] Example 2 1.75 g TiCl4 and 0.8 g SrCl2 were dissolved in 100 ml N,N-dimethylformamide and magnetically stirred at room temperature until fully dissolved. 0.05 g CNT was added to the resulting solution, and triethylamine was slowly added while stirring until the pH reached 9. After the addition was complete, stirring was continued at room temperature for 30 min, followed by standing for 6 h. The mixture was then washed with water and ethanol to obtain a precipitate (i.e., perovskite precursor carbon composite material). The precipitate was dried in an oven at 80 °C for 12 h. The dried precipitate was placed in a tube furnace and heated to 550 °C at 5 °C / min in air atmosphere and held for 2 h to pyrolyze the precursor, forming oxides. After cooling, the oxides were ground into powder to obtain the SrTiO3-CNT composite material. The SrTiO3-CNT composite material was dispersed in methanol, and 1-thioglycerol (mass ratio of SrTiO3-CNT composite material to 1-thioglycerol was 2:3) was added under stirring. The reaction was carried out at room temperature for 3 h to obtain the hydroxyl-modified SrTiO3-CNT composite material.
[0060] The product was characterized by TEM, and the results are as follows: Figure 2 The image shown is a transmission electron microscope (TEM) image of the hydroxyl-modified SrTiO3-CNT composite material.
[0061] Example 3 2.08 g SnCl4 and 0.888 g CaCl2 were dissolved in 100 ml N,N-dimethylformamide and stirred magnetically at room temperature until fully dissolved. 0.08 g CNT was added to the resulting solution. After the addition was complete, stirring was continued at room temperature for 30 min, followed by standing for 6 h. The solution was then washed with water and ethanol to obtain the precipitate. Ethanol provides hydroxyl groups to hydrophilically modify the precipitate. The precipitate was dried in an oven at 80 °C for 12 h.
[0062] The products were characterized using XPS. Figure 3The image shows the X-ray photoelectron spectrum of the hydroxyl-modified SnCaO3-CNT composite material prepared in this embodiment.
[0063] Example 4 1.04 g of SnCl4 and 0.55 g of ZnAc2 were dissolved separately in 100 ml of ethylene glycol and stirred magnetically at room temperature until fully dissolved. 0.1 g of CNT was added to the resulting solution, and polyvinylpyrrolidone was slowly added while stirring to disperse the solution. After the addition was complete, stirring was continued at room temperature overnight, followed by standing for 6 hours. The solution was then washed with water and ethanol to obtain the precipitate. Ethanol provides hydroxyl groups to hydrophilically modify the precipitate. The precipitate was then dried in an oven at 80°C for 12 hours.
[0064] The products were characterized using SEM and EDS. Figure 4 Scanning electron microscope image and elemental distribution map of the hydroxyl-modified SnZnO3-CNT composite material prepared in this embodiment.
[0065] Example 5 1.04 g SnCl4, 0.55 g ZnCl2, and 1.67 g BaCl2 were dissolved in 100 ml of N,N-dimethylformamide and magnetically stirred at room temperature until fully dissolved. 0.02 g CNT was added to the resulting solution, and ethylenediamine was slowly added while stirring until the pH of the solution reached 9. After the addition was complete, stirring was continued at room temperature for 30 min, followed by standing for 6 h. The solution was then washed with water and ethanol to obtain a precipitate (i.e., perovskite precursor carbon composite material). The precipitate was dried in an oven at 80 °C for 12 h. The dried precipitate was placed in a tube furnace and heated to 650 °C at 5 °C / min in an argon atmosphere and held for 2 h. After cooling, it was ground into powder to obtain BaSn. 0.5 Zn 0.5 O3-CNT composite material. The BaSn 0.5 Zn 0.5 The O3-CNT composite material was dispersed in methanol, and 1-thioglycerol (BaSn) was added under stirring. 0.5 Zn 0.5 The O3-CNT composite material was reacted with 1-thioglycerol at a mass ratio of 1:1 at room temperature for 2 hours to obtain the hydroxyl-modified BaSn product. 0.5 Zn 0.5 O3-CNT composite material.
[0066] The products were characterized using XPS. Figure 5A and Figure 5B BaSn modified with hydroxyl groups 0.5 Zn 0.5 X-ray photoelectron spectrum of O3-CNT composite material.
[0067] Example 6 1.04 g NaSnO3·4H2O and 0.55 g ZnAc2 were dissolved in 100 ml dimethyl sulfoxide and magnetically stirred at room temperature until fully dissolved. 0.05 g CNT was added to the resulting solution, and ethylenediamine was slowly added while stirring until the pH of the solution reached 9. After the addition was complete, stirring was continued at room temperature for 30 min, followed by standing for 6 h. The solution was then washed with water and ethanol to obtain the precipitate (i.e., the perovskite precursor carbon composite material). The precipitate was dried in an oven at 80 °C for 12 h. The dried precipitate was placed in a tube furnace and heated to 850 °C at 5 °C / min in air atmosphere and held for 2 h. After cooling, it was ground into powder to obtain the SnZnO3-CNT composite material. The SnZnO3-CNT composite material was dispersed in methanol, and ethylenediaminetetraacetic acid (mass ratio of SnZnO3-CNT composite material to ethylenediaminetetraacetic acid was 1:0.2) was added under stirring. The reaction was carried out at room temperature for 1 h to obtain the carboxyl-modified SnZnO3-CNT composite material.
[0068] The products were characterized using Raman spectroscopy. Figure 6 The image shows the Raman spectrum of the carboxyl-modified SnZnO3-CNT composite material sample.
[0069] Example 7 1.04 g SnCl4, 0.55 g ZnCl2, and 1.67 g CaCl2 were dissolved in 100 ml dimethyl sulfoxide and magnetically stirred at room temperature until fully dissolved. 0.05 g graphene was added to the resulting solution, and ethylenediamine was slowly added while stirring until the pH of the solution reached 9. After the addition was complete, stirring was continued at room temperature for 30 min, followed by standing for 6 h. The solution was then washed with water and ethanol to obtain a precipitate (i.e., perovskite precursor carbon composite material). The precipitate was dried in an oven at 80 °C for 12 h. The dried precipitate was placed in a tube furnace and heated to 850 °C at 5 °C / min in air atmosphere and held for 2 h. After cooling, it was ground into powder to obtain CaSn. 0.5 Zn 0.5 O3-Gr composite material. The CaSn 0.5 Zn 0.5 The O3-Gr composite material was dispersed in methanol, and ethylenediaminetetraacetic acid (CaSn) was added under stirring. 0.5 Zn 0.5 The O3-Gr composite material and ethylenediaminetetraacetic acid (EDTA) were reacted at room temperature for 5 h to obtain the carboxyl-modified CaSn product. 0.5 Zn 0.5 O3-Gr composite material.
[0070] Materials were characterized using XPS. Figure 7 Carboxyl-modified CaSn 0.5 Zn0.5 X-ray photoelectron spectrum of O3-Gr composite material.
[0071] Example 8 1.72 g MnBr2 and 1.47 g MgBr2 were dissolved in 100 ml dimethyl sulfoxide and magnetically stirred at room temperature until fully dissolved. 0.03 g CNT was added to the resulting solution, followed by slow addition of ethylenediamine until the pH reached 9. After the addition was complete, stirring was continued at room temperature for 24 min, followed by standing for 6 h. The solution was then washed with water and ethanol to obtain a precipitate (i.e., perovskite precursor carbon composite material). The precipitate was dried in an oven at 80 °C for 12 h. The dried precipitate was placed in a tube furnace and heated to 850 °C at 5 °C / min in air atmosphere and held for 2 h. After cooling, it was ground into powder to obtain the MgMnO3-CNT composite material. The MgMnO3-CNT composite material was dispersed in methanol, and citric acid (MgMnO3-CNT composite material to citric acid mass ratio 3:1) was added with stirring. The reaction was carried out at room temperature for 0.5 h to obtain the hydroxyl-modified MgMnO3-CNT composite material.
[0072] 450 mg of hydroxyl-modified MgMnO3-CNT composite material and 1 g of NMP solution with 5% PVDF were mixed and stirred into a slurry. The slurry was then coated onto a zinc sheet using a wire rod. The original morphology of the zinc electrode before and after coating with the hydroxyl-modified MgMnO3-CNT composite material was characterized by SEM. Figure 8A and Figure 8B Scanning electron microscope (SEM) images of the original zinc electrode and the zinc electrode surface coated with hydroxyl-modified MgMnO3-CNT composite material, respectively.
[0073] Example 9 1.04 g SnCl4, 0.55 g ZnCl2, and 1.67 g BaCl2 were dissolved in 100 ml of N,N-dimethylformamide and magnetically stirred at room temperature until fully dissolved. 0.05 g graphene was added to the resulting solution, and ethylenediamine was slowly added while stirring until the pH of the solution reached 9. After the addition was complete, stirring was continued at room temperature for 30 min, followed by standing for 6 h. The solution was then washed with water and ethanol to obtain a precipitate (i.e., perovskite precursor carbon composite material). The precipitate was dried in an oven at 80 °C for 12 h. The dried precipitate was placed in a tube furnace and heated to 500 °C at 5 °C / min in air atmosphere and held for 2 h. After cooling, it was ground into powder to obtain BaSn. 0.5 Zn 0.5 O3-Gr composite material. BaSn 0.5 Zn 0.5 The O3-Gr composite material was dispersed in methanol, and 1-thioglycerol (BaSn) was added under stirring. 0.5 Zn 0.5The O3-Gr composite material was reacted with 1-thioglycerol at a mass ratio of 5:1 at room temperature for 1 hour to obtain the hydroxyl-modified BaSn product. 0.5 Zn 0.5 O3-Gr composite material.
[0074] Take 450 mg of hydroxyl-modified BaSn 0.5 Zn 0.5 O3-CNT composite material and 1g of NMP solution with 5% PVDF content were mixed and stirred into a slurry, coated onto a zinc sheet with a wire rod, and assembled into a symmetrical cell. Electrochemical performance was tested and characterized by wetting angle test. Figure 9A and Figure 9B These are the original zinc electrode and the hydroxyl-modified BaSn electrode, respectively. 0.5 Zn 0.5 Comparison of wetting angles on the zinc electrode surface of O3-Gr composite material.
[0075] Example 10 The zinc electrodes coated with the material prepared in Example 1 were assembled in a zinc-zinc symmetrical cell, with both zinc electrodes coated with a hydrophilic perovskite material, the coating facing the separator. The electrolyte was a 2 M ZnSO4 aqueous solution. The polarization state of the cell was measured at room temperature. Figure 10A and Figure 10B The performance graphs of zinc-zinc symmetric cells based on hydrophilic perovskite-coated zinc electrodes and original zinc electrodes at different current densities show that the modified Zn metal cell has a longer cycle life.
[0076] Example 11 The zinc electrodes coated with the material prepared in Example 2 were assembled in a zinc-zinc symmetric cell. Both zinc electrodes were coated with a hydrophilic perovskite material, with the coating facing the separator. The electrolyte was a 2 M ZnSO4 aqueous solution. The polarization state of the symmetric cell at rate was tested. Figure 11 This is a comparison of the rate performance of zinc-zinc symmetric cells based on hydrophilic perovskite-coated zinc electrodes and those based on original zinc electrodes.
[0077] Example 12 The zinc electrodes coated with the material prepared in Example 6 were assembled in a zinc-zinc symmetric cell, with both zinc electrodes coated with a hydrophilic perovskite material so that the coating layer faced the separator. The electrolyte was a 2 M Zn(CF3SO3)2 aqueous solution. The symmetric cell was tested at room temperature after 800 h of deposition and stripping cycles, and the surface morphology of the zinc electrodes was characterized by corrosion roughness. Figure 12A and Figure 12B The images show a comparison of the corrosion roughness of the original zinc electrode and the zinc electrode based on hydrophilic perovskite coating before and after electrochemical testing.
[0078] Example 13 0.8 g TiCl4 and 0.5 g SrCl2 were dissolved in 100 ml N,N-dimethylformamide and magnetically stirred at room temperature until fully dissolved. 0.02 g CNT was added to the resulting solution, and triethylamine was slowly added while stirring until the pH reached 9. After the addition was complete, the mixture was stirred at 0 °C for 30 min, then allowed to stand for 6 h. The solution was then washed with water and ethanol to obtain a precipitate (i.e., perovskite precursor carbon composite material). The precipitate was dried in an oven at 80 °C for 12 h. The dried precipitate was placed in a tube furnace and heated to 650 °C at 5 °C / min in air and held for 12 h to pyrolyze the precursor, forming oxides. After cooling, the oxides were ground into powder to obtain the SrTiO3-CNT composite material. The SrTiO3-CNT composite material was dispersed in methanol, and 1-thioglycerol (mass ratio of SrTiO3-CNT composite material to 1-thioglycerol was 1:3) was added under stirring. The reaction was carried out at room temperature for 0.5 h to obtain the hydroxyl-modified SrTiO3-CNT composite material. Characterization showed that its morphology was similar to that of the product obtained in Example 2.
[0079] Example 14 13g SnCl4, 8g ZnCl2, and 23g BaCl2 were dissolved in 100 ml of N,N-dimethylformamide and magnetically stirred at room temperature until fully dissolved. 0.1g CNT was added to the resulting solution, and ethylenediamine was slowly added while stirring until the pH of the solution reached 9. After the addition was complete, stirring was continued at 80℃ for 30 min, followed by standing for 6 h. The mixture was then washed with water and ethanol to obtain a precipitate (i.e., perovskite precursor carbon composite material). The precipitate was dried in an oven at 80℃ for 12 h. The dried precipitate was placed in a tube furnace and heated to 1000℃ at 5℃ / min in an argon atmosphere and held for 0.5 h. After cooling, it was ground into powder to obtain BaSn. 0.5 Zn 0.5 O3-CNT composite material. The BaSn 0.5 Zn 0.5 The O3-CNT composite material was dispersed in methanol, and 1-thioglycerol (BaSn) was added under stirring. 0.5 Zn 0.5 The O3-CNT composite material was reacted with 1-thioglycerol at a mass ratio of 2:5 at room temperature for 5 hours to obtain the hydroxyl-modified BaSn product. 0.5 Zn 0.5 O3-CNT composite material.
[0080] Example 15 The difference between this embodiment and Example 1 is that CNTs were not added, resulting in the hydrophilic perovskite material ZnSn(OH)6, the TEM structure of which is shown below. Figure 13 As shown.
[0081] The hydrophilic perovskite material ZnSn(OH)6 was used to coat zinc electrodes, which were then assembled in a zinc-zinc symmetric cell. Both zinc electrodes were coated with the hydrophilic perovskite material, with the coating facing the separator. The electrolyte was a 2 M ZnSO4 aqueous solution. The polarization state of the cell was measured at room temperature, and the test results were similar to those in Example 10.
[0082] Example 16 The difference between this embodiment and Embodiment 2 is that CNTs were not added, resulting in a hydroxyl-modified hydrophilic perovskite material SrTiO3.
[0083] The hydroxyl-modified hydrophilic perovskite material SrTiO3 was coated onto a zinc electrode and assembled in a zinc-zinc symmetric cell. Both zinc electrodes were coated with the hydrophilic perovskite material, with the coating facing the separator. The electrolyte was a 2 M ZnSO4 aqueous solution. The polarization state of the symmetric cell at rate was tested. The electrochemical performance test results before and after SrTiO3 modification of the Zn electrode are as follows. Figure 14 As shown.
[0084] Example 17 The difference between this embodiment and Example 6 is that CNTs were not added, resulting in a carboxyl-modified hydrophilic perovskite material, SnZnO3.
[0085] The carboxyl-modified hydrophilic perovskite material SnZnO3 was used to coat zinc electrodes in a zinc-zinc symmetric cell. Both zinc electrodes were coated with the hydrophilic perovskite material, with the coating facing the separator. The electrolyte was a 2 M ZnSO4 aqueous solution. The symmetric cell was tested at room temperature after 800 hours of deposition and stripping cycles. The surface morphology of the zinc electrodes was characterized by SEM. The test results are shown below. Figure 15 As shown.
[0086] In addition, the inventors of this case also conducted experiments with other raw materials, process operations, and process conditions described in this specification, referring to the aforementioned embodiments, and obtained relatively ideal results in all cases.
[0087] It should be understood that the above descriptions are only some embodiments of the present invention. It should be noted that those skilled in the art can make other modifications and improvements without departing from the inventive concept of the present invention, and these all fall within the protection scope of the present invention.
Claims
1. A hydrophilic perovskite material, characterized in that: The chemical formula of the hydrophilic perovskite material is A. x B y X z The A-site element and the B-site element include two or more combinations of K, Na, Mg, Ca, Sr, Ba, Bi, Sn, Pb, Zn, Ti, V, Cr, Mn, Fe, Co, Ni, and Cu. x+y=2, X includes O or OH. When X is O, z=3, and when X is OH, z=6. The surface of the hydrophilic perovskite material has hydrophilic functional groups; Preferably, the hydrophilic functional group includes one or more combinations of hydroxyl, carboxyl, sulfonic acid, and amino groups; Preferably, X may further include doped F element.
2. The method for preparing the hydrophilic perovskite material as described in claim 1, characterized in that, include: A metal salt containing an A-site element, a metal salt containing a B-site element, and a substance that can provide hydrophilic functional groups are uniformly mixed and subjected to a first reaction to obtain a hydrophilic perovskite material. Alternatively, the metal salt containing the A-site element, the metal salt containing the B-site element, and the first organic solvent are uniformly mixed and a second reaction is carried out, and the pH value is adjusted to alkaline to obtain the perovskite precursor. The perovskite precursor is sintered to obtain perovskite material; The perovskite material is subjected to a third reaction with a substance that can provide hydrophilic functional groups to obtain a hydrophilic perovskite material.
3. The preparation method according to claim 2, characterized in that: The metal salt containing the A-site element includes one or more combinations of halide salts and acetates containing the A-site element; and / or, the metal salt containing the B-site element includes one or more combinations of halide salts and acetates containing the B-site element. And / or, the mass ratio of the metal salt containing the A-site element, the metal salt containing the B-site element, and the substance capable of providing hydrophilic functional groups is (0.8~23):(0.5~21):(0.2~5). And / or, the temperature of the first reaction or the second reaction is 0~80℃, and the time is 0.5~18h; And / or, the substances capable of providing hydrophilic functional groups include one or more combinations of thioglycerol, citric acid, ethylenediaminetetraacetic acid, amino-polyethylene glycol-carboxyl, and ethylene glycol; And / or, the first organic solvent includes one or more combinations of N,N-dimethylformamide and dimethyl sulfoxide; And / or, the mass ratio of the metal salt containing the A-site element to the metal salt containing the B-site element is (0.8~23):(0.5~21); And / or, the preparation method includes: adjusting the pH value to alkaline with triethylamine; And / or, the sintering temperature is 500~1000℃, the time is 0.5~12h, and the sintering atmosphere used includes an air atmosphere or an inert atmosphere; And / or, the preparation method includes: dispersing the perovskite material in a second organic solvent, adding a substance capable of providing hydrophilic functional groups under stirring, and carrying out a third reaction at room temperature for 0.5~5 hours to obtain a hydrophilic perovskite material; Preferably, the second organic solvent includes methanol; And / or, the mass ratio of the perovskite material to the substance capable of providing hydrophilic functional groups is (1~12):(0.2~5).
4. A hydrophilic perovskite-carbon composite material, characterized in that, include: The hydrophilic perovskite material and carbon matrix material according to claim 1, wherein the hydrophilic perovskite material and carbon matrix material are uniformly distributed in the carbon matrix material.
5. The hydrophilic perovskite carbon composite material according to claim 4, characterized in that: The carbon matrix material includes one or more of carbon nanotubes, graphene, acetylene black, and Ketjen black; and / or, the content of hydrophilic perovskite material in the hydrophilic perovskite carbon composite material is 30~80 wt%.
6. The method for preparing the hydrophilic perovskite carbon composite material according to any one of claims 4-5, characterized in that, include: A hydrophilic perovskite material is obtained by uniformly mixing a metal salt containing an A-site element, a metal salt containing a B-site element, a carbon matrix material, and a substance that can provide hydrophilic functional groups, and then carrying out a fourth reaction. Alternatively, the metal salt containing the A-site element, the metal salt containing the B-site element, the first organic solvent, and the carbon matrix material are uniformly mixed and subjected to the fifth reaction, and the pH value is adjusted to alkaline to obtain the perovskite precursor carbon composite material. The perovskite precursor carbon composite material is sintered to obtain a perovskite carbon composite material. The perovskite-carbon composite material is subjected to a sixth reaction with a substance that can provide hydrophilic functional groups to obtain a hydrophilic perovskite-carbon composite material.
7. The preparation method according to claim 6, characterized in that: The metal salt containing the A-site element includes one or more combinations of halide salts and acetates containing the A-site element; and / or, the metal salt containing the B-site element includes one or more combinations of halide salts and acetates containing the B-site element. And / or, the mass ratio of the metal salt containing the A-site element, the metal salt containing the B-site element, the carbon matrix material, and the substance capable of providing hydrophilic functional groups is (0.8~23):(0.5~21):(0.02~0.1):(0.2~5); And / or, the temperature of the fourth or fifth reaction is 0~80℃, and the time is 0.5~18h; And / or, the substances capable of providing hydrophilic functional groups include one or more combinations of thioglycerol, citric acid, ethylenediaminetetraacetic acid, amino-polyethylene glycol-carboxyl, and ethylene glycol; And / or, the first organic solvent includes one or more combinations of N,N-dimethylformamide and dimethyl sulfoxide; And / or, the preparation method includes: adjusting the pH value to alkaline with triethylamine; And / or, the mass ratio of the metal salt containing the A-site element, the metal salt containing the B-site element, to the carbon matrix material is (0.8~23):(0.5~21):(0.02~0.1). And / or, the sintering temperature is 500~1000℃, the time is 0.5~12h, and the sintering atmosphere used includes an air atmosphere or an inert atmosphere; And / or, the preparation method includes: dispersing the perovskite carbon composite material in a second organic solvent, adding a substance capable of providing hydrophilic functional groups under stirring, and carrying out a sixth reaction at room temperature for 0.5~5h to obtain the hydrophilic perovskite carbon composite material; Preferably, the second organic solvent includes methanol; And / or, the mass ratio of the perovskite carbon composite material to the substance capable of providing hydrophilic functional groups is (1~23):(0.2~5).
8. The application of the hydrophilic perovskite material of claim 1 or the hydrophilic perovskite carbon composite material of any one of claims 4-5 in the zinc metal anode of a zinc-ion battery.
9. A hydrophilic perovskite coating, characterized in that, The hydrophilic perovskite coating is obtained by coating the hydrophilic perovskite material of claim 1 or the hydrophilic perovskite carbon composite material of any one of claims 4-5 onto the surface of the zinc metal anode. Preferably, the thickness of the hydrophilic perovskite coating does not exceed 20µm.
10. A zinc-ion battery, characterized in that, The zinc metal negative electrode surface of the zinc-ion battery is provided with the hydrophilic perovskite coating as described in claim 9.